Kajian Mekanisme Sulfat Attack pada Struktur Beton terhadap Dampak Siklus Sulfur terhadap Durability Infrastruktur - Aisyah Protonia Tanjung; Lusyana Eka Wardani (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Sulfate attack is a significant chemical degradation mechanism in concrete, particularly for structures located in industrial environments. This process occurs due to reactions between sulfate ions and hydrated cement compounds, such as calcium hydroxide and calcium aluminate, producing expansive products like ettringite and gypsum. The formation of these compounds causes volumetric expansion, cracking, strength reduction, and progressive deterioration of concrete structures. Industrial environments are highly susceptible to sulfate attack due to production activities that generate emissions and wastewater containing sulfur compounds. These sulfur compounds undergo transformation through the environmental sulfur cycle, increasing the availability of aggressive sulfate ions that attack concrete. Continuous sulfate exposure has a significant impact on the durability of concrete infrastructure, characterized by increased porosity and permeability, as well as a reduced service life of structures. This study aims to examine the mechanisms of sulfate attack on concrete structures and its relationship with the sulfur cycle in influencing infrastructure durability. The method employed is a scoping review, analyzing scientific literature from reputable databases and nationally indexed journals. The results indicate that the severity of sulfate attack is influenced by sulfate ion concentration, environmental conditions, and concrete characteristics. A comprehensive understanding of this mechanism provides a critical foundation for the planning, management, and maintenance of sustainable concrete infrastructure in industrial environments.